Active interactions between animals and technology: biohybrid approaches for animal behaviour research - M. Papadopoulou; M. Ball; P. Bartashevich; A.L.J. Burns; V. Chiara; M.A. Clark; B.R. Costelloe; M. Fele; F. French; S. Hauert; M.K. Heinrich; J.E. Herbert-Read; et al. (Animal Behaviour, 2025)

Dissemination and persistence of antimicrobial resistance (AMR) along the wastewater-river continuum - Daniel S. Read; H. Soon Gweon; Michael J. Bowes; Muna F. Anjum; Derrick W. Crook; Kevin K. Chau; Liam P. Shaw; Alasdair Hubbard; Manal AbuOun; Holly J. Tipper; Sarah J. Hoosdally; Mark J. Bailey; et al. (Water Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Projected shifts in fish species dominance in Wisconsin lakes under climate change - Gretchen J. A. Hansen; Jordan S. Read; Jonathan F. Hansen; Luke A. Winslow (Global Change Biology, 2017)
Temperate lakes may contain both coolwater fish species such as walleye ( Sander vitreus ) and warmwater fish species such as largemouth bass ( Micropterus salmoides ). Recent declining walleye and increasing largemouth bass populations have raised questions regarding the future trajectories and management actions for these species. We developed a thermodynamic model of water temperatures driven by downscaled climate data and lake‐specific characteristics to estimate daily water temperature profiles for 2148 lakes in Wisconsin, US , under contemporary (1989–2014) and future (2040–2064 and 2065–2089) conditions. We correlated contemporary walleye recruitment and largemouth bass relative abundance to modeled water temperature, lake morphometry, and lake productivity, and projected lake‐specific changes in each species under future climate conditions. Walleye recruitment success was negatively related and largemouth bass abundance was positively related to water temperature degree days. Both species exhibited a threshold response at the same degree day value, albeit in opposite directions. Degree days were predicted to increase in the future, although the magnitude of increase varied among lakes, time periods, and global circulation models ( GCM s). Under future conditions, we predicted a loss of walleye recruitment in 33–75% of lakes where recruitment is currently supported and a 27–60% increase in the number of lakes suitable for high largemouth bass abundance. The percentage of lakes capable of supporting abundant largemouth bass but failed walleye recruitment was predicted to increase from 58% in contemporary conditions to 86% by mid‐century and to 91% of lakes by late century, based on median projections across GCM s. Conversely, the percentage of lakes with successful walleye recruitment and low largemouth bass abundance was predicted to decline from 9% of lakes in contemporary conditions to only 1% of lakes in both future periods. Importantly, we identify up to 85 resilient lakes predicted to continue to support natural walleye recruitment. Management resources could target preserving these resilient walleye populations.

Genomewide investigation of adaptation to harmful algal blooms in common bottlenose dolphins ( Tursiops truncatus ) - Kristina M. Cammen; Thomas F. Schultz; Patricia E. Rosel; Randall S. Wells; Andrew J. Read (Molecular Ecology, 2015)
Harmful algal blooms ( HAB s), which can be lethal in marine species and cause illness in humans, are increasing worldwide. In the Gulf of Mexico, HAB s of Karenia brevis produce neurotoxic brevetoxins that cause large‐scale marine mortality events. The long history of such blooms, combined with the potentially severe effects of exposure, may have produced a strong selective pressure for evolved resistance. Advances in next‐generation sequencing, in particular genotyping‐by‐sequencing, greatly enable the genomic study of such adaptation in natural populations. We used restriction site‐associated DNA ( RAD ) sequencing to investigate brevetoxicosis resistance in common bottlenose dolphins ( Tursiops truncatus ). To improve our understanding of the epidemiology and aetiology of brevetoxicosis and the potential for evolved resistance in an upper trophic level predator, we sequenced pools of genomic DNA from dolphins sampled from both coastal and estuarine populations in Florida and during multiple HAB ‐associated mortality events. We sequenced 129 594 RAD loci and analysed 7431 single nucleotide polymorphisms ( SNP s). The allele frequencies of many of these polymorphic loci differed significantly between live and dead dolphins. Some loci associated with survival showed patterns suggesting a common genetic‐based mechanism of resistance to brevetoxins in bottlenose dolphins along the Gulf coast of Florida, but others suggested regionally specific mechanisms of resistance or reflected differences among HAB s. We identified candidate genes that may be the evolutionary target for brevetoxin resistance by searching the dolphin genome for genes adjacent to survival‐associated SNP s.

Phytoplankton distribution and nitrogen dynamics in the southwest indian subtropical gyre and Southern Ocean waters - S. J. Thomalla; H. N. Waldron; M. I. Lucas; J. F. Read; I. J. Ansorge; E. Pakhomov (Ocean Science, 2011)
During the 1999 Marion Island Oceanographic Survey (MIOS 4) in late austral summer, a northbound and reciprocal southbound transect were taken along the Southwest Indian and Madagascar Ridge, between the Prince Edward Islands and 31° S. The sections crossed a number of major fronts and smaller mesoscale features and covered a wide productivity spectrum from subtropical to subantarctic waters. Associated with the physical survey were measurements of size fractionated chlorophyll, nutrients and nitrogen (NO3, NH4 and urea) uptake rates. Subtropical waters were characterised by low chlorophyll concentrations (max = 0.27.3 mg m−3 dominated by pico-phytoplankton cells (> 81%) and very low f-ratios (